Evaluasi Kondisi Ekosistem Lamun Thalassia hemprichii Melalui Transplantasi Metode Peat Pot Substrate Modification di Perairan Pantai Desa Suli Kabupaten Maluku Tengah - Rosmawati, Rosmawati; Assagaf, Gamar (INSTITUT AGAMA ISLAM NEGERI AMBON, 2025)
Thalassia hemprichii is a type of seagrass that grows in the coastal waters of Suli Village, Central Maluku Regency and its distribution is quite wide, but its population is starting to decrease considering the damage to the seagrass, including due to the influence of waves and currents which cause the seagrass to be detached from its substrate or damage originating from the activities of the surrounding community such as coastal reclamation, waste pollution and